The role of fascin-1 in the pathogenesis, diagnosis and management of respiratory related cancers - Zhang, Naibin; Gao, Yankun; Bian, Qiang; Wang, Qianqian; Shi, Ying; Zhao, Zhankui; Yu, Honglian (Frontiers in Oncology, 2022)
Human cancer statistics report that respiratory related cancers such as lung, laryngeal, oral and nasopharyngeal cancers account for a large proportion of tumors, and tumor metastasis remains the major reason for patient death. The metastasis of tumor cells requires actin cytoskeleton remodeling, in which fascin-1 plays an important role. Fascin-1 can cross-link F-actin microfilaments into bundles and form finger-like cell protrusions. Some studies have shown that fascin-1 is overexpressed in human tumors and is associated with tumor growth, migration and invasion. The role of fascin-1 in respiratory related cancers is not very clear. The main purpose of this study was to provide an updated literature review on the role of fascin-1 in the pathogenesis, diagnosis and management of respiratory related cancers. These studies suggested that fascin-1 can serve as an emerging biomarker and potential therapeutic target, and has attracted widespread attention.